Post-pandemic recovery strategies of Coastal hotels: Durban, South Africa - Gareeb, Sai-Risha; São João, Erica; Deen, Anisah (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The COVID-19 pandemic caused prevalent effects across multiple industries; the hotel industry in parti-cular was impacted severely. However, Durban hotels derived innovative recovery strategies that could be implemented in most hospitality operations to alleviate financial disruptions. Furthermore, exemplifies the significance of hotel preparedness in times of crisis. This study aims to investigate the effects and recovery strategies post-COVID-19 in Durban hotels to present recommendations to sustain the industry through disastrous events. A qualitative methodology was applied in the primary data collection through semi-structured interviews with hotel general and senior managers. Qualitative computer-assisted software known as ATLAS.ti was used in the data analysis. The findings indicate that the measures taken by hotels resulted in sustainable strategies that aided their survival through the pandemic. Strategies included marketing campaigns, competition analysis, tactical spending, and evolved offerings among others. This paper provides achievable practices that can be used in times of crisis or financial challenges for hotels irrespective of status or size.